THE INFLUENCE OF PERSONAL FACTORS AND IN STORE FACTORS TOWARD IMPULSE BUYING BEHAVIOR TO URGE TO BUY IMPULSIVELY AT SEPHORA PAKUWON MALL SURABAYA - Sholihatun Nashihah SE (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
This research aims to examine the influence of Personal Factor (Money Availability,Time Availability, Family Influence, Economic Well Being, Credit Card Use) and InStoreFactor(SalesPromotion,StoreEnvironment,Music,FriendlyEmployee)TowardImpulseBuyingBehaviortoUrgetoBuyImpulsivelyontheconsumerofSEPHORAPakuwonMall Surabaya. This research was conducted on consumers of SEPHORAPakuwon Mall Surabaya by using the primary data method. The questionnaires weredistributed directly to the consumers of SEPHORA Pakuwon Mall Surabaya usingGoogle docs/form. This questionnaire had been distributed to as much as 161 selectiverespondents who experienced impulsive buying at SEPHORA Pakuwon Mall Surabaya.The sampling technique used was purposive sampling and the research instruments weretested using PLS analysis which employed steps of the outer model test, inner modeltest and hypothesis test. The result of the data analysis from PLS showed that ThePersonal Factors has insignificant influence toward Impulse Buying Behavior and Urgeto Buy Impulsively on the customers of SEPHORA Pakuwon Mall Surabaya, In-StoreFactor has significant influence toward Urge to Buy Impulsively on the customers ofSEPHORA Pakuwon Mall Surabaya, and Urge to Buy Impulsively give insignificant effect toward Impulse Buying Behavior on the consumers of SEPHORA Pakuwon MallSurabaya.